2015
DOI: 10.1128/iai.00936-15
|View full text |Cite
|
Sign up to set email alerts
|

LL-37 Immunomodulatory Activity during Mycobacterium tuberculosis Infection in Macrophages

Abstract: Tuberculosis is one of the most important infectious diseases worldwide. The susceptibility to this disease depends to a great extent on the innate immune response against mycobacteria. Host defense peptides (HDP) are one of the first barriers to counteract infection. Cathelicidin (LL-37) is an HDP that has many immunomodulatory effects besides its weak antimicrobial activity. Despite advances in the study of the innate immune response in tuberculosis, the immunological role of LL-37 during M. tuberculosis inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 31 publications
4
62
1
6
Order By: Relevance
“…Exogenous LL-37 decreases TNF-α and IL-17 while inducing antiinflammatory IL-10 and TGF-β production in a monocyte-derived macrophage cell line infected with Mycobacterium tuberculosis [82]. However, the decreased production of anti-inflammatory cytokines does not reduce anti-mycobacterial activity supporting the concept that LL-37 modulation of cytokines is independent of the P2X7 receptor.…”
Section: Human Cathelicidinsmentioning
confidence: 57%
“…Exogenous LL-37 decreases TNF-α and IL-17 while inducing antiinflammatory IL-10 and TGF-β production in a monocyte-derived macrophage cell line infected with Mycobacterium tuberculosis [82]. However, the decreased production of anti-inflammatory cytokines does not reduce anti-mycobacterial activity supporting the concept that LL-37 modulation of cytokines is independent of the P2X7 receptor.…”
Section: Human Cathelicidinsmentioning
confidence: 57%
“…Several studies have confirmed that vitamin D induces hCAP18 expression in cultured human macrophages [21], [24], [31], [32]. However many clinical studies have failed to show a positive effect of vitamin D on the treatment of tuberculosis infection [33].…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, a recent study investigated the therapeutic potential of LL-37 in modulating macrophage-mediated excessive inflammatory responses. It was found that LL-37 reduced the severity of tuberculosis by rapidly enhancing the anti-inflammatory cytokine TGF-β, IL-10, and prostaglandin E from the infected macrophages [128]. However, further studies regarding the exogenous effect of LL-37 in severe pulmonary tuberculosis are warranted.…”
Section: Molecular Mechanisms Of Anti-and Pro-inflammatory Action Of mentioning
confidence: 99%